New family Apotomouridae fam. nov. (Coleoptera: Tenebrionoidea) from lower Cenomanian amber of Myanmar. (November 2018) - Bao, Tong; Walczyńska, Katarzyna S.; Moody, Samantha; Wang, Bo; Rust, Jes
Abstract: The new family Apotomouridae fam. nov. (Coleoptera: Polyphaga: Tenebrionoidea) is described based on Multispinus multispinosus gen. et sp. nov. and Apotomoura fortiscrura gen. et. sp. nov. from Burmese amber (lower Cenomanian, ca. 99 Ma). The retractile wedge-shaped body and tarsal formula 5-5-4 placed Apotomouridae fam. nov. in Tenebrionoidea. The new family shares similarities with the Mordellidae, whereas the absence of pygidium and the combination of other microstructures assigned it more closely to the Jurassic beetle genus Wuhua . The morphological characters suggest the similar flower feeding style as to Mordellidae and Ripiphoridae, which represent the flower diet and pollinating strategy in the Tenebrionoidea.